Measurement of Radiographers’ Pandemic Experiences and Perceptions During COVID-19 - AlMulla, Muna (Archives of Clinical and Biomedical Research, 2022)
COVID-19 is a recent globally-manifested phenomenon that compels healthcare workers to face and rapidly adapt to forceful changes. While much of the research has a general focus on all healthcare professions,this work has the specific focus on radiographers because they play a critical role in monitoring the spread of COVID-19. A Pandemic Experiences and Perceptions Survey (PEPS) was used to report on radiographers’ experiences. A cross-sectional questionnaire survey was distributed to radiographers between May and June 2020. A number of 102 (29.4%) completed the survey (48 [47.1%] males and 54 [52.9%] females). With respect to the five PEPS tools, the means (± SD) of each tool were as follows: disruption, 2.487 (±0.94); resources, 2.576 (±0.914); risk perception, 2.946 (±1.57); impact on work-life areas, 3.81 (±0.711); and leadership, 3.795 (±0.807). Eighty percent of radiographers were in agreement that COVID-19 affected their work distribution and 74.5% did not consider their protective equipment, staff availability, and support staff competence to be adequate. Sixty-two percent of the participants reported fear of the virus. This study allows for front-line radiographers to quickly express concerns and provides insight into the issues that must be addressed during the current and future outbreaks.